Contributions of complementary therapies and other strategies for the treatment of depression: an integrative review (Research, Society and Development, 2022)
Depression today, faced with the eventualities of life, has become a common and recurrent disease and in order to improve the quality of life or even combat the adverse effects arising from the use of medication, many depressive patients have opted for the use of complementary therapies or alternatives. Thus, the present research had as main objective to present the complementary therapies that have been used for the treatment of depression. For this, an integrative review was carried out with a survey of works in the following data platforms PubMed, Scientific Electronic Library Online (Scielo), Virtual Health Bank (BVS) and Google Scholar. Papers published in the last 5 years in Portuguese, English and Spanish were considered for the research. A total of 15 articles were found through the search and the main therapies used were the use of probiotics, supplements and curcumin, and the performance of auriculotherapy, music therapy, mindfulness, community therapy, yoga, Reiki, meditation, electroacupuncture, acupuncture, aromatherapy, biofeedback, hypnosis, homeopathy, light therapy, massage therapy, dance, spiritual and religious intervention, therapy based on Chinese movements, pilates and aerobic training. In conclusion, it was observed that there are studies that buy the benefits of alternative therapies, however, in view of the great variety of methodologies and samples, more randomized clinical trials should be carried out in order to reaffirm them.